2010
DOI: 10.1523/jneurosci.1324-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

POSH is an Intracellular Signal Transducer for the Axon Outgrowth Inhibitor Nogo66

Abstract: Myelin-derived inhibitors limit axon outgrowth and plasticity during development and in the adult mammalian CNS. Nogo66, a functional domain of the myelin-derived inhibitor NogoA, signals through the PirB receptor to inhibit axon outgrowth. The signaling pathway mobilized by Nogo66 engagement of PirB is not well understood. We identify a critical role for the scaffold protein Plenty of SH3s (POSH) in relaying process outgrowth inhibition downstream of Nogo66 and PirB. Blocking the function of POSH, or two POSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 38 publications
2
45
1
1
Order By: Relevance
“…Recent studies confirmed that the scaffold proteins of SH3s (POSH), actin-myosin regulatory protein SHROOM3, and Rho Kinase (ROCK) have been involved in the downstream signaling pathways of PirB to participate in the inhibition of neuronal outgrowth (Dickson et al, 2010;Taylor et al, 2008). The important downstream molecules in the PirB pathway were also observed in the present study.…”
Section: Expression Of Posh Shroom3 Rock1 and Rock2 In Tle Patientssupporting
confidence: 88%
“…Recent studies confirmed that the scaffold proteins of SH3s (POSH), actin-myosin regulatory protein SHROOM3, and Rho Kinase (ROCK) have been involved in the downstream signaling pathways of PirB to participate in the inhibition of neuronal outgrowth (Dickson et al, 2010;Taylor et al, 2008). The important downstream molecules in the PirB pathway were also observed in the present study.…”
Section: Expression Of Posh Shroom3 Rock1 and Rock2 In Tle Patientssupporting
confidence: 88%
“…Therefore, we hypothesized that pharmacological inhibition of the Shroom3/ROCK2 protein–protein interaction with CCG-17444 would relieve neurite outgrowth inhibition, as observed for RNA interference (RNAi) mediated reduction of POSH or Shroom3 function [14, 16]. To test this hypothesis, we examined the effect of compound treatment on neurite outgrowth in differentiated neurons derived from mouse P19 embryonic carcinoma cells [14, 16, 21, 22]. Neurons were generated by transfection with the neural basic helix-loop-helix protein Neurogenin 2 (Ngn2) [16, 21].…”
Section: Resultsmentioning
confidence: 99%
“…This signaling complex includes the actin-myosin regulator Shroom3, Rho kinase, and leucine zipper kinase (LZK or MAP3K12) [14, 16]. Shroom3 directly binds to Rho kinase [1619].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we will focus on polymorphisms in CLOCK,39 NPAS2,40 PER2,41 PER3,42 PDE4D,43 MUC1,44 ATP2B1,44 45 DCDC5,44 TRPM6,44 SHROOM344 46 and MDS144 genes, which are associated with sleepiness, sleep phase and potentially respiratory muscle weakness. If consent is received for the genetic study, blood is drawn and stored prior to transport to the Center for Human Genetic Research at Massachusetts General Hospital where blood samples will be processed and genetic analysis performed.…”
Section: Ethics and Disseminationmentioning
confidence: 99%